Endometrial Cancer 2022
DOI: 10.1136/ijgc-2022-esgo.251
|View full text |Cite
|
Sign up to set email alerts
|

2022-RA-859-ESGO Long-term survival outcomes in high-risk endometrial cancer patients undergoing sentinel lymph node biopsy vs. lymphadenectomy

Abstract: was not associated with DFS (p=0.518) (Hazard ratio (HR) 1.20 95% CI 0.688-2.100). We found differences according to the surgical approach for OS (p<0.043) with an HR of 1.63 (95% CI: 1.104-1.63). There is 1.63 times more risk of death in the laparotomy approach. 38 (49.35%) of the laparotomies were performed in the first 5 years of the series, patients died from other causes not due to cancer (18 (60%) versus 22 (37.9%) in the laparoscopy group p=0.049). We have compared OS with cancer-specific death in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The majority of extrauterine spread in endometrial cancer involves the retroperitoneal lymph nodes. In a retrospective study from Italy on high-risk early-stage patients with endometrial cancer, the observed occurrence was 3.3% in both pelvic and p a r a -a o r t i c l y m p h n o d e s i n t h o s e w h o u n d e r w e n t lymphadenectomy (7). In the evaluation of uncommon lymph node recurrence other than the above sites, an earlier single institutional study of 22 patients with endometrial cancer documented the first recurrence sites to be the inguinal, supraclavicular, and axillary lymph nodes (8).…”
Section: Discussionmentioning
confidence: 97%
“…The majority of extrauterine spread in endometrial cancer involves the retroperitoneal lymph nodes. In a retrospective study from Italy on high-risk early-stage patients with endometrial cancer, the observed occurrence was 3.3% in both pelvic and p a r a -a o r t i c l y m p h n o d e s i n t h o s e w h o u n d e r w e n t lymphadenectomy (7). In the evaluation of uncommon lymph node recurrence other than the above sites, an earlier single institutional study of 22 patients with endometrial cancer documented the first recurrence sites to be the inguinal, supraclavicular, and axillary lymph nodes (8).…”
Section: Discussionmentioning
confidence: 97%
“…Whether endometrial cancer patients require lymphadenectomy or other procedures such as sentinel lymph node mapping, pelvic lymphadenectomy alone or combined pelvic and para-aortic lymphadenectomy is still controversial. [16][17][18] Previously, the presence of lymph node metastasis was identified to influence the prognosis and treatment decisions of patients with endometrial cancer. 19 The molecular subtype and preoperative cancer antigen 125> 25 were significantly associated with lymph node metastasis in patients with endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…When these high-risk factors are consistent, the location of the primary tumor is also highly correlated with the location of lymph node metastasis. Capozzi et al [49] revealed Regarding the primary outcome, only the tumor pattern diffused to the whole uterine cavity was statistically associated with SLN uptake on common iliac lymph nodes (OR 2.4,95%CI 1e5.8, p ¼ 0.05).…”
Section: Relationship Between Tumor Location and Lymph Node Metastasi...mentioning
confidence: 98%